Analysis of the powers and forms of activity of public authorities in the field of state financial control of Ukraine - Naboka, Liudmyla; Tsovma, Bohdan (Theory and Practice of Public Administration, 2025)
The article examines the ongoing transformations in the functional arrangements of public authorities engaged in state financial control in Ukraine under the influence of digital transformation. A number of systemic problems that reduce the quality of control activities have been identified, including the duplication of powers among control bodies, the absence of clear regulatory delineation of functions, weak interagency coordination, and insufficient implementation of the results of control measures.The study identifies the main forms of financial control: inspection, financial audit, procurement verification, monitoring and outlines the methods used for their implementation. The functional characteristics of key state financial control institutions, such as the Accounting Chamber, the Ministry of Finance of Ukraine, the State Audit Service, the State Tax Service of Ukraine, and the State Treasury Service of Ukraine, as well as their territorial units are analysed with attention to their legal and administrative interaction.The research substantiates the need to introduce an integrated digital control model that combines these forms on the basis of a unified information platform. It proposes ways to strengthen regulatory accountability for non-compliance with the recommendations of control bodies and mechanisms for enhancing transparency and accountability in the sphere of public financial management.The results of the study have applied value for designing strategies to improve state financial control in the context of digitalisation, decentralisation, and the strengthening of the state’s economic security.